Do Corticosteroids Still Have a Place in the Treatment of Chronic Pain? - Knezevic, Nebojsa Nick; Jovanovic, Filip; Voronov, Dimitry; Candido, Kenneth D. (Frontiers in Pharmacology, 2018)
Corticosteroids have played a standard role in the multimodal pain management in the treatment of chronic spinal pain (cervical and lumbar) and osteoarthritis pain over the past three decades. In this review we discuss different types of injectable steroids that are mainly used for injection into the epidural space (for the treatment of radicular back and neck pain), and as intraarticular injections for different types of osteoarthritis related pain conditions. Furthermore, we discuss different approaches taken for epidural corticosteroid injections and spinal surgical rates when injections fail to resolve painful conditions, as well as the possibility of using local anesthetics alone for neuraxial injections, instead of in combination with corticosteroids. While we present some beneficial effects of newly available treatment options for low back pain and osteoarthritis pain, such as use of PRP and hyaluronic acid, corticosteroids remain important considerations in the management of these chronic pain conditions.